Polyketide synthase gene pksM from Aspergillus terreus expressed during growth phase - Pazoutová, S; Linka, M; Storková, S; Schwab, H (Folia microbiologica, 1997)
The polyketide synthase gene pksM was detected in the genomic DNA library of Aspergillus terreus by hybridization with the 6-methylsalicylic acid synthase (6-MSAS) gene of Penicillium patulum as a probe. 9524 bp of the cloned DNA were sequenced and a 5.5 kb open reading frame was revealed. A single intron (62 bp) was identified in the conserved position. Two transcription start points were determined within the 5'-flanking region at 50 and 72 (major) bp upstream from the putative translation initiation codon ATG. The conserved active site motifs for ketosynthase, acyltransferase, dehydratase, ketoreductase and acyl carrier protein were found within the predicted polypeptide consisting of 1803 amino acids. Unlike the P. patulum 6-MSAS gene, the transcription of pksM from A. terreus was observed in the middle of the vegetative growth phase.
Keywords: Molecular Sequence Data; Sequence Analysis, DNA; sekvence aminokyselin; Alcohol Oxidoreductases; DNA sondy; dehydratasy; beta-ketoacyl-ACP-reduktasa; Acyl Carrier Protein; Multienzyme Complexes; protein přenášející acyl; Introns; Open Reading Frames; hybridizace nukleových kyselin; Sequence Alignment; Penicillium; DNA fungální; polymerázová řetězová reakce; Polymerase Chain Reaction; fungální RNA; Hydro-Lyases; multienzymové komplexy; Ligases; geny hub; Nucleic Acid Hybridization; 3-oxoacylsynthasa; ligasy; 3-Oxoacyl-(Acyl-Carrier-Protein) Reductase; Transcription, Genetic; Cloning, Molecular; DNA Probes; genetická transkripce; Acyltransferases; Base Sequence; sekvence nukleotidů; restrikční mapování; 3-Oxoacyl-(Acyl-Carrier-Protein) Synthase; kodon iniciační; Gene Expression; Codon, Initiator; Gene Library; Amino Acid Sequence; Oxidoreductases; otevřené čtecí rámce; DNA, Fungal; Plasmids; Aspergillus; northern blotting; klonování DNA; sekvenční analýza DNA; Restriction Mapping; plazmidy; exprese genu; acyltransferasy; introny; molekulární sekvence - údaje; sekvenční homologie aminokyselin; Blotting, Northern; Genes, Fungal; genová knihovna; sekvenční seřazení; alkoholoxidoreduktasy; RNA, Fungal; Sequence Homology, Amino Acid; oxidoreduktasy